Challenges and Prospects of Evaluation of Programs in Public Finance Management in Georgia - D. Oboladze; R. Otinashvili (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The establishment of a program assessment mechanism in the public sector of Georgia is an important element for supporting the ongoing public finance management reform and improving the budgeting process as well as enhancing the budget planning stage and ensuring the efficient, productive and prudent management of budgetary means. The present paper discusses the problem of the absence of a program assessment mechanism in the public sector, reviews alternative solutions to the problem and, by applying a cost-effective method, analyzes the best alternative. This best alternative envisages the establishment of a centralized structural unit at the Ministry of Finance which will be responsible for the assessment of the programs/subprograms of ministries/budgetary organizations. The concluding part of the policy paper offers those measures and reforms in the form of recommendations which must be undertaken for the successful implementation of the best alternative.